Benthic hypoxia in anthropogenically-impacted rivers provides positive feedback enhancing the level of bioavailable metals at sediment-water interface. (March 2020) - Jaiswal, Deepa; Pandey, Jitendra
Abstract: We investigated the effect of hypoxic-anoxic range of dissolved oxygen (DO) on metal release/bioavailability at sediment-water interface (SWI) in the Ganga River. Here, we consider eight sites in the main river stem along 518 km; sixty sites downstream two point sources and two tributary confluences covering 630 km; and an incubation experiment to verify these results. We found higher concentrations of metals and bioavailable fractions at SWI at two locations of main stem and up to 700 m, 1000 m, 400 m and 500 m downstream Assi drain, Wazidpur drain, Ramganga confluence and Varuna confluence respectively where DO at SWI (DOsw ) was <2.0 mgL −1 . The incubation experiment did show higher levels of metal- and P-release and bioavailability under anoxic-hypoxic range of DO. The risk assessment code and eutrophication index indicated high to very high risks of contaminated river sediment and water to aquatic environment at sites with hypoxic-anoxic range of DOsw . Further, the principal component analyses separated metals and bioavailable fractions opposite to FDAase indicating greater risk at these locations. The study, which forms the first report on benthic hypoxia/anoxia-driven metal release, potential bioavailability and risk to the Ganga River ecosystem will help understanding how human-driven perturbations influence geochemical cycling of metals and ecosystem responses in large rivers. Graphical abstract: Image 1 Highlights: Effect of hypoxic-anoxic range of DO on sediment-metal release/bioavailability was investigated. Sites with DOsw  < 2.0 mgL −1 showed high metal-release/bioavailability at sediment-water interface. The incubation studies did show sediment-metal- and P-release in concordance with decreasing DO. A series of biomarkers of effects indicated risks of toxicity at sites with high metal release/bioavailability. First report linking benthic hypoxia/anoxia to metal-release, bioavailability and ecosystem response shift in Ganga River. Abstract : This study forms first report on benthic hypoxia/anoxia-driven sediment-metal release/bioavailability and associated shifts in ecosystem response of the Ganga River.